Portfolio assessment: Learning outcomes and students’ attitudes - Teguh Sulistyo; Katharina Poptrisia Nona Eltris; Siti Mafulah; Suhartawan Budianto; Saiful Saiful; Dwi Fita Heriyawati (Studies in English Language and Education, 2020)
This paper is aimed at (1) investigating whether the implementation of portfolio assessment had an impact on students’ writing ability, and (2) obtaining the students’ attitudes towards portfolios. The method used in this study was quasi-experimental research design, and the data were collected through a set of writing tests (pre-test and post-test) and a questionnaire. The results show that the implementation of portfolio assessment increased the students’ writing ability. It was also found that the students’ knowledge of global issues (content and organization) also increased more significantly than the local issues (grammar, vocabulary, and mechanics). In addition, the results of the questionnaire proved that the secondary level students had positive attitudes towards the implementation of the portfolio assessment. Therefore, it is suggested that the portfolio assessment should be implemented in the teaching-learning process especially in English writing since it could give regular feedback, and help the students in monitoring their writing progress.